Dukungan Informasional Keluarga Berpengaruh dalam Pemberian ASI Eksklusif di Desa Timbulharjo Sewon Bantul - Nur Indah Rahmawati (Jurnal Ners dan Kebidanan Indonesia, 2016)
Infant Mortality Rate (IMR) in Indonesia according to the Demographic and Health Survey (IDHS) reached IMR was 32 per 1.000 live births in 2012. Research WHO states that 88% of child mortality linked to malnutrition, which is often associated with the intake of milk. Family is the closest person who can help the mother to give exclusive breastfeeding. For that family support is very important in the success of exclusive breastfeeding. The aim of research to determine the relationship of the family with the informational support exclusive breastfeeding in the village Timbulharjo, Sewon, Bantul. This study was observational analytic cross sectional approach. This study uses the 76 respondents who had infants aged 6-24 months that follow posyandu in Timbulharjo village in April-May with a purposive sampling techniques. The instrument used in this study was a questionnaire. Data were obtained subsequently analyzed using frequency distribution table, chi square as percentages and odds ratios (OR). The results of this study indicate that there is a significant relationship between the informational support to the families with exclusive breastfeeding correlation value chi square p=0.000 mothers who get no good informational support 16 times more likely to not memberikasn exclusive breastfeeding her baby. Conclusion There is a significant relationship between emotional support in the family with exclusive breastfeeding in the village Timbulharjo, Sewon, Bantul.